Si and Ca foliar evaluation in the growth and tolerance to foliar necrosis complex in oil palm nurseries. - Garbanzo, Gabriel (2018)
The evaluation of different sources of silicon and Calcium foliar in the growth and tolerance of diseases in oil palm nurseries it was evaluate in the pacific south of Costa Rica. Different sources of foliar Si and Ca were applied to oil palm nurseries and it was evaluated the effect in foliar necrosis complex (Complejo de Necrosis Foliar in Spanish, CNF) severity. The experiment consisted to aspersion on leaves of four Ca sources, three Si sources and one Ca source with phytoalexins. The experiment design was a randomized complete block with 9 treatments and 4 repetitions. The experiment variables evaluated were the morphological growth and % of CNF at 85, 130, 175, 220, 265 and 300 days after planting (dds). Also, it was evaluated the foliar concentration of N, P, K, Ca, Mg, S, Fe, Zn, Mn, Cu, B and Si at 175, 220, 265 y 300 dds. It was found that the application of foliar Si and Ca did not show a significant effect on CNF tolerance over time. The foliar Si concentration and Ca did not show significant difference. The SupCu treatment increased the concentration of Cu in the plant and this decreased significantly the CNF. Also, it was found that sources with K and P in form of phosphites increased probably the growth of the plant of oil palm. It was concluded that the foliar fertilizers with Ca and Si were not effective for CNF control, but the Cu sources, these probably could increase the tolerance to CNF.